STRATEGI KAMPANYE CROWDFUNDING PERSUASIF LEMBAGA SOSIAL DALAM MELAKUKAN GERAKAN SOSIAL BERDERMA - Winda Dwi Astuti Zebua; Syifa Astasia Utari; Abdul Rahman; Sucianty Ramadhanty (Perspektif Komunikasi Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2025)
This article aims to analyze the persuasive crowdfunding campaign strategies carried out by the social organization Ketimbang Ngemis Jakarta (KNJ) in the charitable social movement through Instagram. Grounded in Pope's (2023) theory, three key factors determine campaign success: communication strategy, credibility and transparency, and audience engagement. The research adopts a qualitative approach, utilizing in-depth interviews, online observation, and social media content analysis. Findings reveal KNJ's effective optimization of these factors. First, its communication strategy leverages visual content and emotional narratives (e.g., the story of Mr. Leo) to foster empathy and donor participation. Second, credibility and transparency are maintained through organizational legality, periodic reporting, and internal verification mechanisms for aid accuracy. Third, audience engagement is cultivated via two-way interactions, Instagram's interactive features, and public involvement in beneficiary recommendations. However, challenges such as donor fatigue and fraud risks persist. The study's outcomes offer a framework for other social organizations to optimize digital-era crowdfunding campaigns, emphasizing the synergy of emotionally compelling communication, robust credibility, and active audience participation.